2009
DOI: 10.1073/pnas.0901351106
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical cross-resistance betweenBacillus thuringiensistoxins Cry1Ac and Cry2Ab in pink bollworm

Abstract: Transgenic crops producing Bacillus thuringiensis (Bt) toxins kill some key insect pests and can reduce reliance on insecticide sprays. Sustainable use of such crops requires methods for delaying evolution of resistance by pests. To thwart pest resistance, some transgenic crops produce 2 different Bt toxins targeting the same pest. This ''pyramid'' strategy is expected to work best when selection for resistance to 1 toxin does not cause cross-resistance to the other toxin. The most widely used pyramid is trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
107
3
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(115 citation statements)
references
References 58 publications
4
107
3
1
Order By: Relevance
“…The first kind of pleiotropic effect can be named cross-infectivity by analogy to cross-resistance of microbes, insects, or weeds to different (bio)chemical compounds in a medical or agricultural context (35)(36)(37)(38)(39). It can be defined as the effect of a single mutational event which leads to the breakdown of at least two plant resistance genes or alleles, an initial one, which exerts selection pressure on the pathogen population leading to the fixation of an RB mutation, and a second one, which does not play any role in the fixation of the RB mutation.…”
Section: Discussionmentioning
confidence: 99%
“…The first kind of pleiotropic effect can be named cross-infectivity by analogy to cross-resistance of microbes, insects, or weeds to different (bio)chemical compounds in a medical or agricultural context (35)(36)(37)(38)(39). It can be defined as the effect of a single mutational event which leads to the breakdown of at least two plant resistance genes or alleles, an initial one, which exerts selection pressure on the pathogen population leading to the fixation of an RB mutation, and a second one, which does not play any role in the fixation of the RB mutation.…”
Section: Discussionmentioning
confidence: 99%
“…The gene pyramiding strategy to combine Cry1Ac and Cry2Ab has proven to be effective in delaying the development of insect resistance to Bt toxins (25,26). Nonetheless, resistance to Cry2Ab has been reported in Heliothis virescens, Helicoverpa zea, Helicoverpa armigera, Helicoverpa punctigera, Pectinophora gossypiella, and Trichoplusia ni (8,(27)(28)(29)(30)(31)(32). These reports have indicated that Cry2Ab-resistant alleles are present in insect populations, and the frequency of resistant alleles will increase with selection.…”
mentioning
confidence: 91%
“…The concerns regarding the environmental impact of GE plants include those worries related to their possible invasiveness in ecosystems (Snow et al 2005); outcrossing and horizontal gene transfer (Yao et al 2008, Rong et al 2010); development of resistant pest populations that would again require the input of pesticides (Tabashnik et al 2009); and effects on nontarget organisms (NTOs). In the case of IRGE plants, effects on NTOs is a particular concern, as these organisms provide important ecosystem services such as biological control (predators and parasitoids), pollination, and decomposition (Kennedy 2008, Romeis et al 2008a.…”
mentioning
confidence: 99%